Strategi Manajemen Ekuitas Merek Pada Usaha Mikro Dalam Menghadapi Persaingan Marketplace (Studi Kasus Martabak Stecu Tikung) - agung susilo bintang gumelar; Nadyah Lutvia Ningsih; Chintya Dwi Oktavia; Adinda Berliana Eka Aprilia (Jurnal Ekonomi dan Bisnis Digital, 2026)
The rapid growth of digital marketplaces has fundamentally transformed the competitive landscape of micro-enterprises, particularly in the culinary sector where product similarity and price competition are highly prevalent. In this context, brand equity has become a critical intangible asset that determines the sustainability and competitiveness of micro-businesses. This study aims to analyze brand equity management strategies implemented by Martabak Stecu Tikung, a micro-scale culinary enterprise, in responding to marketplace competition. This research adopts a qualitative approach using a case study method to capture in-depth and contextual insights into brand management practices.Data were collected through in-depth interviews with the business owner, direct observation of digital marketing activities, and documentation of product displays, promotional content, and customer reviews on marketplace platforms. Data analysis was conducted using descriptive qualitative techniques, including data reduction, data presentation, and conclusion drawing, supported by triangulation to ensure data validity.The findings reveal that Martabak Stecu Tikung manages its brand equity through four interrelated dimensions: brand awareness, brand association, perceived quality, and brand loyalty. Brand awareness is strengthened through consistent visual identity, distinctive brand naming, and active engagement on social media. Brand associations are developed through product differentiation, innovative menu variants, and a modern culinary image. Perceived quality is reinforced by consistent taste, quality ingredients, attractive presentation, and positive customer reviews. Brand loyalty is built through responsive service, promotional incentives, and satisfactory customer experiences. This study concludes that systematic and consistent brand equity management enables micro-enterprises to enhance competitiveness and maintain market relevance in increasingly competitive digital marketplaces.